Aspects of the biology, thermal physiology and nutritional ecology of Pareuchaetes insulata (Walker) (Lepidoptera: Erebidae: Arctiinae), a specialist herbivore introduced into South Africa for the biological control of Chromolaena odorata (L.) King and Robinson (Asteraceae) - Uyi, Osariyekemwen (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2015)
Chromolaena odorata (L.) King and Robinson (Asteraceae) is an invasive weedy shrub native to the Americas that has proven to be a significant economic and ecological burden to many tropical and sub-tropical regions of the world where it impacts negatively on agriculture, biodiversity and livelihoods. A distinct biotype of C. odorata was first recognised as naturalized in KwaZulu-Natal (KZN) province, South Africa, in the 1940s and has since spread to other climatically suitable provinces. Pareuchaetes insulata (Walker) (Lepidoptera: Erebidae: Arctiinae) was released in KZN, South Africa, as a biological control agent against the weed between 2001 and 2009. Although the moth did establish at one out of some 30 release sites, its population level is generally low in the field. This thesis attempts to unravel the reasons for the poor performance of P. insulata in South Africa.Studies of life history traits of P. insulata in the laboratory indicated that the moth possess good biological attributes such as low mortality, high fecundity, egg hatchability and high female mating success. Overall, adult female moths eclosed before their male counterparts suggesting the presence of protogyny. Beyond the contribution of this study to our understanding of the life history traits of erebid moths, it hypothesized that the absence of protandry might have contributed to the low population levels of the moth in the field. To determine if a degree of agent-host plant incompatibility is culpable for the poor performance of P. insulata, insect performance metrics were compared on two distinct C. odorata plants (one from Florida and another from South Africa) in laboratory experiments. Pareuchaetes insulata performance metrics were similar on both plant forms; there were no significant differences in total leaf area consumed, egg and larval development, immature survival rates, feeding index (FI), host suitability index (HSI), growth index (GI), and fecundity between the Floridian and southern African C. odorata plants. In sum, there was no evidence to demonstrate that differences in plant forms in C. odorata are culpable for the poor performance of P. insulata in South Africa.The effects of temperature on the developmental and reproductive life history traits, locomotion performance and thermal tolerance range of P. insulata were studied in order to elucidate the possible role of temperature on the poor performance of the moth. The results showed that at temperatures below 25 °C, mortality increased and development time was prolonged. Fecundity and egg hatchability were negatively affected at a constant temperature of 15 °C. Results futher showed that third instar larvae were unable to initiate movement at 6 °C and locomotor abilities were significantly reduced at 11 °C. In sum, it is hypothesized that both direct and indirect negative impacts of low temperature may partly explain the poor performance of P. insulata in South Africa. Theeffects of seasonal and spatial variations in the leaf characteristics of C. odorata on the performance of P. insulata were investigated. Foliar nitrogen and magnesium concentrations were higher in shaded plants during winter due to low temperatures. Leaves of C. odorata plants growing in the shaded habitat (relative to full sun) and leaves of plants during autumn (relative to winter) were more nutritionally balanced and suitable for herbivore performance. Consequently, P. insulata developed faster, had heavier pupal mass and increased fecundity when reared on shaded leaves (relative to full sun) or when reared on autumn leaves compared to leaves growing in winter. This study demonstrates that low winter temperatures can indirectly affect insect herbivore performance by changing the phytochemistry of host plant and hypothesized that excess nitrogen and possibly magnesium may have detrimental effects on the insect herbivore performance.A cross-feeding experiment was conducted to determine P. insulata response to a change in the diet of offspring due to a shift in plant quality in shaded versus full sun habitats. The results showed that a 'negative switch' in herbivore diet (i.e. when progeny from parents reared on shaded leaves were fed on full sun leaves) resulted in high (40%) mortality, prolonged development time and reduced fecundity. Thus full sun foliage is an inferior diet for P. insulata offspring. In laboratory experiments, foliar nitrogen was positively correlated with the performance of P. insulata. From this study, it is demonstrably evident that the poor performance of P. insulata on C. odorata in South Africa is caused by multiple factors such as low temperatures as well as spatio-temporal variations in the leaf characteristic of C. odorata leaves. This study shows the complexity of determining the causes of low populations and apparent low impact of biological control agents and herbivorous insects generally, in the field. The implications of this research to the biological control programme against C. odorata and the direction of future research for the control of C. odorata are discussed.
Keywords: Chromolaena odorata; Chromolaena odorata -- Biological control -- South Africa; Arctiidae